2013
DOI: 10.1186/1471-2458-13-857
|View full text |Cite
|
Sign up to set email alerts
|

Increasing condom use and declining STI prevalence in high-risk MSM and TGs: evaluation of a large-scale prevention program in Tamil Nadu, India

Abstract: BackgroundThis paper presents an evaluation of Avahan, a large scale HIV prevention program that was implemented using peer-mediated strategies, condom distribution and sexually transmitted infection (STI) clinical services among high-risk men who have sex with men (HR-MSM) and male to female transgender persons (TGs) in six high-prevalence state of Tamil Nadu, in southern India.MethodsTwo rounds of large scale cross-sectional bio-behavioural surveys among HR-MSM and TGs and routine program monitoring data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 25 publications
1
29
0
1
Order By: Relevance
“…They are also beginning to examine the factors that affect HIV testing and engagement in care and treatment. An increase in research and a scale-up of combination prevention programs tailored for transgender women will be necessary to effectively address the HIV epidemic among transgender women [56]. …”
Section: Resultsmentioning
confidence: 99%
“…They are also beginning to examine the factors that affect HIV testing and engagement in care and treatment. An increase in research and a scale-up of combination prevention programs tailored for transgender women will be necessary to effectively address the HIV epidemic among transgender women [56]. …”
Section: Resultsmentioning
confidence: 99%
“…In Tamil Nadu, transgender women (20–40% were TSW) had reductions in both syphilis and HIV prevalence after implementation of the programme compared with baseline. 73 …”
Section: Interventions To Prevent Hiv Infectionmentioning
confidence: 99%
“…New, current, or history of STI is strong indicators of previous or current exposure to unsafe sexual practice; which is the primary major risk factor for HIV acquisition and transmission. Subramanian et al (2013) documented a significant decline in STI prevalence and stable HIV prevalence in India. This was due to a large scale HIV prevention program targeting safer sexual practices among high-risk MSM in high-prevalence state of Tamil Nadu [43].…”
Section: Risk Factors For Incidencementioning
confidence: 99%
“…Subramanian et al (2013) documented a significant decline in STI prevalence and stable HIV prevalence in India. This was due to a large scale HIV prevention program targeting safer sexual practices among high-risk MSM in high-prevalence state of Tamil Nadu [43]. Two recent randomized clinical trials successfully demonstrated that antiretroviral drugs can be used for HIV prevention.…”
Section: Risk Factors For Incidencementioning
confidence: 99%